SOME RESULTS ON CONNECTED ACCURATE EDGE DOMINATION IN FUZZY GRAPHS USING STRONG ARCS - GANI, A. NAGOOR; RAHMAN*, A. ARIF (International Journal of Mathematical Archive, 2018)
In this paper, connected accurate edge dominating set of a fuzzy graph is discussed. An accurate edge dominating set D is said to be a connected accurate edge dominating set, if an induced fuzzy subgraph <D> of G is connected. The connected accurate edge domination number,Â is the minimum fuzzy cardinality taken over all connected accurate edge dominating sets of G. We also determine, upper bounds of connected accurate edge domination number for some standard fuzzy graphs. Relations between connected accurate edge domination number and some other edge domination parameters are discussed.